2015
DOI: 10.1007/s00168-015-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

Industrial structure and total factor productivity: the Tunisian manufacturing sector between 1998 and 2004

Abstract: Using a panel of manufacturing firms operating in 138 delegations across the Tunisian coast and observed over the 1998-2004 period, we study the impact of industrial structure on regional economic growth measured by total factor productivity. The results of an unbalanced panel data-based model indicate that the diversity of the industrial scene seems to be a local growth-promoting factor for high-tech sectors. Specialization often articulates the impact of diversity, while competition positively affects produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…All these theories confirm that agglomeration affects the production within firms and the development of urban areas and national competitiveness. Externalities have a role on reducing production costs, improving innovation and enhancing total factor productivity [22][23][24][25].…”
Section: Industrial Agglomerationmentioning
confidence: 99%
See 1 more Smart Citation
“…All these theories confirm that agglomeration affects the production within firms and the development of urban areas and national competitiveness. Externalities have a role on reducing production costs, improving innovation and enhancing total factor productivity [22][23][24][25].…”
Section: Industrial Agglomerationmentioning
confidence: 99%
“…where N i denotes urban employment and K i denotes physical capital stock. Previous studies have concluded that infrastructure, human capital, foreign direct investment (FDI), capital investment, research and development and information communication are important factors affecting total factor productivity [22,[54][55][56][57]. The total factor productivity can be calculated as follows:…”
Section: Theoretical Framework Analysismentioning
confidence: 99%
“…Since Marshall's concept of industrial scale of economies does not mention the interaction of the scale of economies between industries, and vice versa, Jacob's concept does not restrict any industrial specialization, it is possible that diversity and specialization could be considered in separate frameworks. For instance, Batisse (2002) and Thabet (2015) consider specialization as a ratio between a share of industry within a zone and a share of industry from the whole country, while diversity is separately defined as an inverse of normalized HHI of industry concentration. Paci and Usai (1999) and Van Der Panne (2004) measure industrial diversity by index based on a reciprocal of the Gini index.…”
Section: Methodsmentioning
confidence: 99%
“…Despite past studies considering specialization/diversity in separate variables, they could be intuitively considered together with the same index, as they can be viewed as opposing factors to each other. The index used in Batisse (2002) and Thabet (2015) shows that diversity is defined as an index of industry concentration, and this concentration can be also considered as specialization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation